2018
DOI: 10.3389/fnmol.2018.00473
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Properties and Physiological Functions of Recoverin

Abstract: Recoverin (Rcv) is a low molecular-weight, neuronal calcium sensor (NCS) primarily located in photoreceptor outer segments of the vertebrate retina. Calcium ions (Ca2+)-bound Rcv has been proposed to inhibit G-protein-coupled receptor kinase (GRKs) in darkness. During the light response, the Ca2+-free Rcv releases GRK, which in turn phosphorylates visual pigment, ultimately leading to the cessation of the visual transduction cascade. Technological advances over the last decade have contributed significantly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…Probably PYGM is involved in the inactivation, recovery, and/or regulation of the phototransduction cascade through interaction with recoverin (RCVRN) and CALM1, both connected with Ca 2+ cellular level regulation. The RCVRN, a low-molecular-weight, neuronal calcium sensor, is involved in phototransduction cascade regulation and signal transmission in a calcium-dependent manner [ 32 , 35 ]. So far, no experimental data explain the exact role of PYGM in this process.…”
Section: The Biological Importance Of Pygmmentioning
confidence: 99%
“…Probably PYGM is involved in the inactivation, recovery, and/or regulation of the phototransduction cascade through interaction with recoverin (RCVRN) and CALM1, both connected with Ca 2+ cellular level regulation. The RCVRN, a low-molecular-weight, neuronal calcium sensor, is involved in phototransduction cascade regulation and signal transmission in a calcium-dependent manner [ 32 , 35 ]. So far, no experimental data explain the exact role of PYGM in this process.…”
Section: The Biological Importance Of Pygmmentioning
confidence: 99%
“…Unveiling the detailed structural mechanisms underlying the Rec function may lead to useful generalizations to other NCS proteins, considering the prototypical role of Rec as a myristoyl-switch protein [2]. A number of experimental studies based on NMR [5,28,38,45], surface plasmon resonance [7,12,46,47] and dynamic light scattering [48,49] all confirmed that the binding of two Ca 2+ ions to the functional motifs EF2 and EF3 in Rec triggers the myristoyl switch process, which by extruding the acyl chain from the protein milieu leads to the significant exposure of a hydrophobic crevice eventually necessary to accommodate the GRK1 target.…”
Section: Discussionmentioning
confidence: 99%
“…The small (23 kDa) Ca 2+ -binding protein recoverin (Rec) is a prototypical member of the neuronal calcium sensor (NCS) family mostly expressed in vertebrate photoreceptors, where it plays a role in the regulation of the phototransduction cascade [1,2]. Light triggers a transient drop in the intracellular concentration of Ca 2+ and such change is promptly detected by a group of calcium sensors including Rec, which reversibly bind to specific targets in a Ca 2+ -dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…It is a unique protein that uses a calcium–acyl switch for regulated membrane attachment and probable association with interactors similar to the protein recoverin. Recoverin is a neuronal calcium sensor, mainly expressed in retinal photoreceptors [81,82]. It is myristoylated in the calcium-bound state and associates with the plasma membrane via interactors.…”
Section: Double Acylation: Myristoylation and Palmitoylationmentioning
confidence: 99%